Trabecular Meshwork Motion Profile from Pulsatile Pressure Transients: A New Platform to Simulate Transitory Responses in Humans and Nonhuman Primates - Chen Xin; Xiaofei Wang; Ningli Wang; Ruikang Wang; Murray Johnstone (Applied Sciences, 2021)
Trabecular meshwork (TM) motion abnormality is the leading cause of glaucoma. With technique limitations, how TM moves is still an enigma. This study describes a new laboratory platform to investigate TM motion responses to ocular transients in ex vivo eyes. The anterior segments of human cadaver and primate eyes were mounted in a perfusion system fitting. Perfusion needles were placed to establish mean baseline pressure. A perfusion pump was connected to the posterior chamber and generated an immediate transient pressure elevation. A phase-sensitive optical coherent tomography system imaged and quantified the TM motion. The peak-to-peak TM displacements (ppTMD) were determined, a tissue relaxation curve derived, and a time constant obtained. This study showed that the ppTMD increased with a rise in the pulse amplitude. The ppTMD was highest for the lowest mean pressure of 16 mmHg and decreased with mean pressure increase. The pulse frequency did not significantly change ppTMD. With a fixed pulse amplitude, an increase in mean pressure significantly reduced the time constant of recoil from maximum distension. Our research platform permitted quantitation of TM motion responses to designed pulse transients. Our findings may improve the interpretation of new TM motion measurements in clinic, aiding in understanding mechanisms and management.